2005
DOI: 10.1029/2004ja010581
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sheet turbulence observed by Cluster II

Abstract: [1] Cluster fluxgate magnetometer (FGM) and ion spectrometer (CIS) data are employed to analyze magnetic field fluctuations within the plasma sheet during passages through the magnetotail region in the summers of 2001 and 2002 and, in particular, to look for characteristics of magnetohydrodynamic (MHD) turbulence. Power spectral indices determined from power spectral density functions are on average larger than Kolmogorov's theoretical value for fluid turbulence as well as Kraichnan's theoretical value for MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
138
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 44 publications
(159 reference statements)
12
138
1
Order By: Relevance
“…Such has been the case, for instance, for the measured fields in the solar wind, magnetospheric cusp, plasma sheet and the auroral zone (Burlaga, 1991;Bruno et al, 2001;Weygand et al, 2005;Tam et al, 2005;Echim et al, 2007). The origin of intermittent fluctuations in magnetized plasmas was interpreted as the result Correspondence to: S. W. Y.…”
Section: Introductionmentioning
confidence: 99%
“…Such has been the case, for instance, for the measured fields in the solar wind, magnetospheric cusp, plasma sheet and the auroral zone (Burlaga, 1991;Bruno et al, 2001;Weygand et al, 2005;Tam et al, 2005;Echim et al, 2007). The origin of intermittent fluctuations in magnetized plasmas was interpreted as the result Correspondence to: S. W. Y.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows the scatter plots of the spectral indices α for all of the 47 events. The indices are presented for three pairs of two different components, so that a degree of anisotmulti-spacecraft observations from Cluster, Weygand et al (2005) were able to estimate turbulent eddy scale sizes in association with magnetic field fluctuations in the plasma sheet. Voros et al (2004) introduced a wavelet technique to study magnetic turbulence, as obtained from the same Cluster satellite observations.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Stepanova et al, (2005aStepanova et al, ( , 2005b have found that the intermittency has strong magnetic local time behaviour being significantly stronger close to the substorm eye. Weygand et al (2005) have also found that both the scaling behavior of the probability distribution functions and the multifractal structure function suggest that intermittent MHD turbulence is present within the plasma sheet. This paper strives to look at the intermittency of the magnetospheric dynamics from a slightly different angle.…”
Section: Introductionmentioning
confidence: 92%